Population density predicts outcome from out-of-hospital cardiac arrest in Victoria, Australia - Nehme, Z.; Andrew, E.; Cameron, P.; Bray, Janet; Bernard, S.; Meredith, I.; Smith, K. (2014)
Objective: To examine the impact of population density on incidence and outcome of out-of-hospital cardiac arrest (OHCA). Design, setting and participants: Data were extracted from the Victorian Ambulance Cardiac Arrest Registry for all adult OHCA cases of presumed cardiac aetiology attended by the emergency medical service (EMS) between 1 January 2003 and 31. December 2011. Cases were allocated into one of five population density groups according to their statistical local area: very low density (= 10 people/km2), low density (11-200 people/km2), medium density (201-1000 people/km2), high density (1001-3000 people/km2), and very high density (> 3000 people/km2). Main outcome measures: Survival to hospital and survival to hospital discharge. Results: The EMS attended 27 705 adult presumed cardiac OHCA cases across 204. Victorian regions. In 12 007 of these (43.3%), resuscitation was attempted by the EMS. Incidence was lower and arrest characteristics were consistently less favourable for lower population density groups. Survival outcomes, including return of spontaneous circulation, survival to hospital and survival to hospital discharge, were significantly poorer in less densely populated groups (P < 0.001 for all comparisons). When compared with very low density populations, the risk-adjusted odds ratios of surviving to hospital discharge were: low density, 1.88 (95% CI, 1.15-3.07); medium density, 2.49 (95% CI, 1.55-4.02); high density, 3.47 (95% CI, 2.20-5.48) and very high density, 4.32 (95% CI, 2.67-6.99). Conclusion: Population density is independently associated with survival after OHCA, and significant variation in the incidence and characteristics of these events are observed across the state.